2006
DOI: 10.1063/1.2185640
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of domain walls in BaTiO3 using simultaneous atomic force and piezo response force microscopy

Abstract: In this letter a method to simultaneously measure the physical and the polarization thickness of a 90°d omain wall in a ferroelectric perovskite is presented. This method combines accurate atomic force microscopy and piezoresponse force microscopy scans of the same area with little drift and an analysis of the entire scanned area. It is found that the physical thickness is significantly narrower ͑about seven and a half times͒ than the polarization thickness in a 90°domain wall in BaTiO 3 . Evidence of the trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
3
11
0
Order By: Relevance
“…4, where in steady state, the dopants segregate along a domain wall in an asymmetric manner creating a defect dipole. Recent simultaneous AFM-PFM measurements of emerging 90 domain walls in BaTiO 3 show that the physical width is significantly smaller (over 7 times) than the piezoelectric width consistent with longrange electrostatic interactions [21]. Further, the decoration of the domain wall with defects is consistent with experimental observations of Shilo et al [22] and provides a mechanism for the domain wall to have a memory of its location during annealing.…”
Section: Prl 95 247603 (2005) P H Y S I C a L R E V I E W L E T T E supporting
confidence: 70%
“…4, where in steady state, the dopants segregate along a domain wall in an asymmetric manner creating a defect dipole. Recent simultaneous AFM-PFM measurements of emerging 90 domain walls in BaTiO 3 show that the physical width is significantly smaller (over 7 times) than the piezoelectric width consistent with longrange electrostatic interactions [21]. Further, the decoration of the domain wall with defects is consistent with experimental observations of Shilo et al [22] and provides a mechanism for the domain wall to have a memory of its location during annealing.…”
Section: Prl 95 247603 (2005) P H Y S I C a L R E V I E W L E T T E supporting
confidence: 70%
“…[5][6][7][8][9] This is one of the main reasons, which together with the clamping effect of the substrate, 10,11 is used to explain the often reported immobility or low mobility of twins in ferroelectric films. In agreement with the analysis of Ishibashi, Franck et al 18 found that the polarization width of a 90°domain wall is much thicker ͑about 7.5 times͒ than the physical width, which was estimated to be 10 nm. 13 In the past few years, several publications were dedicated to theoretical and experimental investigations of atomistic structure [14][15][16] and polarization reversal processes 17,18 of 90°domain walls.…”
supporting
confidence: 83%
“…25 Therefore, it is reasonable to attribute the enhancement of the piezoelectric coefficient shown through the largest d 33 -V curve in Fig. 16,18,27 In summary, a spatial variation of the d 33 piezoelectric coefficient measured on ferroelectric capacitors was observed for PZT films possessing a c / a / c domain structure. The inset in Fig.…”
mentioning
confidence: 80%
“…(3). Different domains (having different state P and e) are separated by very narrow domain walls (Shilo et al, 2004;Franck et al, 2006) in which P and e gradually change from one preferred state to another.…”
Section: Potential Energymentioning
confidence: 99%